Resistance training and energy balance - Poehlman, E. T.; Melby, Ch. (International Journal of Sport Nutrition and Exercise Metabolism, 1998)
In this brief review we examine the effects of resistance training on energy expenditure. The components of daily energy expenditure are described, and methods of measuring daily energy expenditure are discussed. Cross-sectional and exercise intervention studies areexamined with respect to their effects on resting metabolic rate, physical activity energy expenditure, postexercise oxygen consumption, and substrate oxidation in younger and older individuals